Biochemical Response to a Moderate Running Bout in Participants With or Without a History of Acute Knee Injury - Cattano, Nicole M. (J Athl Train, 2017)
CONTEXT: : Individuals with an acute knee-injury history are 4 times more likely to develop knee osteoarthritis than those without a prior knee injury, and it is unknown why. Individuals with an injury history may exhibit aberrant changes in tissue turnover after physical activity (eg, running), which could lead to osteoarthritis, but this has yet to be determined among young, physically active individuals. OBJECTIVE: : To determine collagen degradation and synthesis and inflammatory biomarker concentration levels before exercise and changes in response to an acute running bout in injured participants compared with healthy control participants. DESIGN: : Cohort study. SETTING: : Research laboratory. PATIENTS OR OTHER PARTICIPANTS: : A total of 22 physically active individuals between 18 and 25 years of age were recruited for the study: 11 injured participants (knee injury within 4 years of the study) who were medically cleared for physical activity and 11 matched healthy control participants. MAIN OUTCOME MEASURE(S): : The independent variable was group (injured or control). Dependent variables were serum biomarker concentrations for cartilage oligomeric matrix protein, matrix metalloproteinase-13, proinflammatory marker interleukin-1β, c-terminal cross-linking telopeptide of type II collagen, and type II collagen synthesis marker. Each participant provided prerun and postrun blood samples for biomarker-concentration analysis. RESULTS: : No group differences existed in serum biomarker concentrations before exercise or in serum biomarker changes from pre-exercise to postexercise. CONCLUSIONS: : After an acute bout of moderate-intensity running, young, active individuals in a high-risk postinjury population had similar biochemical responses as matched healthy controls. However, the external generalizability of these findings to other exercises and populations has yet to be determined.